Numerical simulation of droplet generation characteristics in T-confined microchannel - YUAN Yuejin; CAO Xiaoge; ZHAO Yu; HE Yongqing; XU Yingying (Xi'an Gongcheng Daxue xuebao)
To provide reference for controlling the generation of uniform high frequency of droplets, aimed at droplet generation in confined microchannels, considering the influence of fluid physical properties and flow conditions, numerical simulation of droplet formation in a T-confined microchannel was carried out. Using COMSOL software, droplet generation process simulation model was established, and the phase field method was adopted to explore the capillary number, two-phase flow ratio, viscosity ratio and wall wettability effects on droplet generation. Results showed that when the continuous phase viscosity is 0.01 Pa·s, and the dispersed phase velocity and viscosity are 0.005 m/s and 0.001 Pa·s, respectively, as the continuous phase capillary number increases from 0.001 5 to 0.007 5, the continuous phase capillary number increased from 0.0015 to 0.0075, the dimensionless droplet length decreased from 2.8 power index to 1.5, the dimensionless liquid column length increased linearly from 2.6 to 7.6, the droplet generation frequency increased from 30 power exponents per second to 52; when the continuous phase viscosity is 0.01 Pa·s, the dispersed phase viscosity is 0.001 Pa·s, and the flow ratio increased from 0.1 to 0.9, the dimensionless droplet length increased linearly from 1.05 to 2.55, the dimensionless liquid column length decreased from 6.49 power index to 2.51, the droplet generation frequency decreased from 170 power index per second to 65, when the continuous phase velocity is 0.01 m/s, the dispersed phase velocity is 0.005 m/s, and the viscosity ratio increased from 0.025 to 0.5, and the dimensionless droplet length increased from 1.72 to 2.1 The length of the dimensionless liquid column increased from 3.11 to 3.9, and the droplet generation frequency decreased from 31 functions per second to 24. Wall wettability affects the morphology of droplets, but there is no obvious functional relationship. The physical properties and flow conditions of fluid have significant influence on droplet formation.